(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Employing a descriptive-survey research design with diverse learners, the study surveyed respondents using a structured questionnaire focusing on the AI tools they use, and the level of responsible AI use. Data analysis through descriptive statistics, particularly weighted mean and standard deviation was used. The findings revealed that most students use Grammarly, ChatGPT, Canva AI tools, and Quillbot. While respondents generally showed awareness and concern about bias and fairness in AI tools, there is a need to improve their responsible AI use particularly in reporting bias instances and reducing over- reliance on AI. Additionally, while recognizing the importance of personal accountability and critical thinking alongside AI use, implementation varied. Overall, the findings stress the ongoing need to promote responsible AI use in educational environments, highlighting the significance of education and awareness in fostering ethical and equitable AI practices. The researchers recommend using advocacy material to improve the responsible use of AI among the respondents.